Which Learning Activities Enhance Physical Therapist Practice? Part 2: Systematic Review of Qualitative Studies and Thematic Synthesis. Issue 9 (11th June 2020) - Leahy, Edmund; Chipchase, Lucy; Calo, Marlena; Blackstock, Felicity C
Abstract: Objective: Post-professional physical therapy expertise requires career-long participation in learning activities. Understanding physical therapists' lived experience of learning activities provides novel insight into how best to enhance physical therapist practice from the perspective of the learner. The purpose of this study was to explore qualified physical therapists' experiences, beliefs, and perspectives with regard to learning activities and professional development. Methods: Eight databases were searched for studies published from inception through December 2018. Study selection included mixed-methods and qualitative studies exploring physical therapists' experiences, perspectives, beliefs, and attitudes. Thematic synthesis was performed, and the GRADE-Confidence in the Evidence from Reviews of Qualitative research was used to assess the level of confidence in the findings. A total 41 studies with 719 participants were included. Results: The key findings include physical therapists' perceptions that worthwhile post-professional learning requires more than attendance at professional development courses. Physical therapists perceived that worthwhile learning requires connection with others and being "taken out of one's comfort zone." Sufficient time and accessible, trustworthy resources were also valued. Conclusions: Moderate- to low-level evidence suggests that the choice of professional development activities and education design for qualified physical therapists should consider the inclusion of connected activities, activities that take participants out of comfort zones, time to practice, and trustworthy resources that are easily accessible. Future research should evaluate the effectiveness of learning activities encompassing these factors, prioritizing those that minimize the barriers of time and distance. Impact: This study adds to the profession's understanding of physical therapists' lived experience of learning activities, providing novel insight into how best to enhance physical therapist practice from the perspective of the learner.